2022
DOI: 10.1109/access.2022.3144841
|View full text |Cite
|
Sign up to set email alerts
|

Transmittance Multispectral Imaging for Reheated Coconut Oil Differentiation

Abstract: Oil reheating has a significant impact on global health due to its extensive consumption, especially in South Asia, and severe health risks. Nevertheless, food image analysis using multispectral imaging systems(MISs) has not been applied to oil reheating analysis despite their vast application in rapid food quality screening. To that end, the paper discusses the application of a low-cost MSI to estimate the 'reheat cycle count classes' (number of times an oil sample is recursively heated) and identify 'critica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The efficacy of support vector regression in CPO price forecasting is emphasized, and it is suggested that by employing feature selection techniques and adding more pertinent attributes, future research can improve accuracy. Zhao, 2022 [10] The application of machine-learning and Raman spectroscopy for the rapid detection of edible oils type and adulteration 19 Rapid detection of edible oils type and adulteration.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of support vector regression in CPO price forecasting is emphasized, and it is suggested that by employing feature selection techniques and adding more pertinent attributes, future research can improve accuracy. Zhao, 2022 [10] The application of machine-learning and Raman spectroscopy for the rapid detection of edible oils type and adulteration 19 Rapid detection of edible oils type and adulteration.…”
Section: Resultsmentioning
confidence: 99%
“…The Covid-19 pandemic has caused an unparalleled crisis in the tourism industry economy (Gerszon et al, 2020). Due to the negative impact of the corona virus, some repercussions were recorded, most notably: biggest drop ever in the numbers of the employees working in tourism and hospitality sector (workforce reduction), Massive job cuts and pay cuts, encouragement to from home, reservations have been cancelled, giving employees mandatory leave, making employees to perform extra works ‫والفنادق‬ ‫السياحة‬ ‫كلية‬ ‫جملة‬ -‫عدد‬ 41 -‫ديسمرب‬ 0202 (Ranasinghe et al, 2021). The corona virus has caused severe economic damage in various countries of the world, which requires governments to act immediately to support people and businesses.…”
Section: Literature Reviewmentioning
confidence: 99%